Linking cellular stress responses to systemic homeostasis. Issue 11 (November 2018) - Galluzzi, Lorenzo; Yamazaki, Takahiro; Kroemer, Guido
Abstract Mammalian cells respond to stress by activating mechanisms that support cellular functions and hence maintain microenvironmental and organismal homeostasis. Intracellular responses to stress, their regulation and their pathophysiological implications have been extensively studied. However, little is known about the signals that emanate from stressed cells to enable a coordinated adaptive response across tissues, organs and the whole organism. Considerable evidence has now accumulated indicating that the intracellular mechanisms that are activated in response to different stresses — which include the DNA damage response, the unfolded protein response, mitochondrial stress signalling and autophagy — as well as the mechanisms ensuring the proliferative inactivation or elimination of terminally damaged cells — such as cell senescence and regulated cell death — are all coupled with the generation of signals that elicit microenvironmental and/or systemic responses. These signals, which involve changes in the surface of stressed cells and/or the secretion of soluble factors or microvesicles, generally support systemic homeostasis but can also contribute to maladaptation and disease. Cellular stress responses primarily serve to rectify stress-associated damage. However, these responses are also coupled with the generation of various signals that are transmitted to the cellular microenvironments or even across tissues. This communication generally supports the maintenance of systemic homeostasis but can also result in pathology.